Mengemas Cita Rasa dalam Ruang Digital : Representasi Kuliner Lokal Kota Palopo di Instagram - Nuthy Hasya Afifah; Jingga Ayu Azzahra; Bahtiar; Hidayanti; Rahamwati (Jurnal Kaganga: Jurnal Ilmiah Sosial dan Humaniora, 2026)
Local culture in its development is also influenced by social media. One of the ways is illustrated by the presence of regional culinary accounts as information media that depict cultural image and identity. This study aims to understand the form of local culinary representation and the process of forming the meaning of local culinary through content uploaded to the Instagram account palopo.kuliner. This study uses a descriptive qualitative approach with Stuart Hall's media and culture theory. Data collection techniques were carried out through observation of Instagram content, documentation in the form of upload screenshots, and interviews with the account manager and followers of the Instagram account palopo.kuliner. Data analysis was carried out by looking at the form of local culinary representation through photos, videos, captions, and the use of everyday language, as well as the encoding and decoding processes in forming the meaning of the content. The results of the study indicate that the Instagram account palopo.kuliner represents local culinary of Palopo City not only as a consumer product, but also as a cultural identity and a promotional medium for local (UMKM). This representation is realized through attractive food visuals as a form of encoding, a natural dining atmosphere as a form of encoding to show the meaning of authenticity, the use of informative captions as a form of encoding that helps the audience interpret (decode) the meaning displayed, and everyday language as an encoding to build closeness with the audience.